2012
DOI: 10.2215/cjn.06990711
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerance of Urea Compared with Vaptans for Long-Term Treatment of Patients with SIADH

Abstract: SummaryBackground and objectives Vaptans (vasopressin V 2 -receptor antagonists) are a new approach for the treatment of hyponatremia. However, their indications remain to be determined, and their benefit compared with that of the usual treatments for the syndrome of inappropriate antidiuretic hormone secretion (SIADH) have not been evaluated. This prospective, long-term study compared the efficacy, tolerability, and safety of two oral vaptans with those of oral urea in patients with SIADH.Design, setting, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(63 citation statements)
references
References 48 publications
0
61
0
2
Order By: Relevance
“…We found several case series demonstrating an increase in serum sodium concentration after 2-7 days for urea (202,203,204,205,206), demeclocycline (207), loop diuretics in combination with oral NaCl (123,125,208), phenytoin (209) and fluid restriction (210). We also identified case series of patients experiencing an increase in serum sodium over a longer time period of up to 12 months for urea (211,212,213), up to 3 weeks for demeclocycline (214,215,216,217,218,219), up to 20 weeks for lithium (220), up to 150 days for furosemide with oral NaCl (221) and up to 30 days in phenytoin (220).…”
Section: Rationale † Why This Question?mentioning
confidence: 89%
“…We found several case series demonstrating an increase in serum sodium concentration after 2-7 days for urea (202,203,204,205,206), demeclocycline (207), loop diuretics in combination with oral NaCl (123,125,208), phenytoin (209) and fluid restriction (210). We also identified case series of patients experiencing an increase in serum sodium over a longer time period of up to 12 months for urea (211,212,213), up to 3 weeks for demeclocycline (214,215,216,217,218,219), up to 20 weeks for lithium (220), up to 150 days for furosemide with oral NaCl (221) and up to 30 days in phenytoin (220).…”
Section: Rationale † Why This Question?mentioning
confidence: 89%
“…It does so by inducing a solute (urea) diuresis that, by increasing urine flow rate, decreases the concentration of sodium and potassium in the urine and hence increases excretion of electrolyte-free water (22). Although a recent study by Soupart and colleagues in 13 patients with SIADH found that urea was as effective in raising serum sodium levels and was as well tolerated as the vasopressin antagonist tolvaptan (23), in my experience and in informal surveys of practicing nephrologists in North America, urea is not widely used in North America, primarily because of limited availability. There is no US Pharmacopeia-approved formulation, and it is not available at most pharmacies.…”
Section: Ureamentioning
confidence: 99%
“…Urea powder may be obtained from the pharmacy. This modality is very cost effective and has been used to correct hyponatremia in SIADH slowly, by 2-3 mmol/liter/day, a rate comparable to the effect of water restriction [Decaux, 2001;Soupart and Decaux, 2009]. An easy procedure is to dissolve 15-30 g of urea in a glass of orange juice and to administer two or three glasses a day after meals.…”
Section: Treatment Of Siadh Using General and Indirect Meansmentioning
confidence: 99%